Validação de técnicas de avaliação reprodutiva de fêmeas de vida-livre de tamanduá-bandeira (Myrmecophaga tridactyla) e tatu-canastra (Priodontes maximus) - Lobo, Ana Carolina Monteirinho [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
The giant anteater (Myrmecophaga tridactyla) and the giant armadillo (Priodontes maximus) are classified as vulnerable to extinction. The application of reproductive biotechnologies represents a promising strategy for conservation; however, their effective implementation depends on detailed knowledge of the reproduction of these species. In this context, the present study integrated methodologies well established in domestic species, including external genital evaluation, vaginal cytology, serum estradiol and progesterone assays, and vaginal microbiota characterization, to assess the reproductive status of juvenile and adult free-living females of M. tridactyla and P. maximus in the Cerrado and Pantanal biomes. Between 2023 and 2025, 13 giant anteater females and six giant armadillo females were evaluated. In M. tridactyla, vaginal cytology revealed a predominance of parabasal and intermediate cells. Mean estradiol concentrations were 21.38 ± 8.75 pg/mL in adults and 27.38 ± 17.30 pg/mL in juveniles, while progesterone concentrations were 1.97 ± 0.76 ng/mL and 2.42 ± 0.75 ng/mL, respectively, with no significant differences between groups. The vaginal microbiota showed a relatively homogeneous composition, predominantly consisting of bacilli from the family Enterobacteriaceae. In P. maximus, wide variation in external genital morphology was observed. Vaginal cytology of the juvenile female was characterized by a predominance of parabasal cells, whereas adult females exhibited greater cytological heterogeneity. Mean estradiol and progesterone concentrations in adults were 422.5 ± 620.4 pg/mL and 5.8 ± 3.3 ng/mL, respectively, while values in the juvenile were 10.2 pg/mL and 1.8 ng/mL. Significant correlations were identified among morphological, cytological, and hormonal parameters, and the vaginal microbiota was predominantly composed of bacilli from the family Enterobacteriaceae. These results provide preliminary foundations for the development of reproductive monitoring protocols for these species.

O tamanduá-bandeira (*Myrmecophaga tridactyla*) e o tatu-canastra (*Priodontes maximus*) são espécies classificadas como vulneráveis à extinção, e a aplicação de biotecnologias reprodutivas surge como estratégia promissora para sua conservação, embora dependa do conhecimento detalhado da reprodução desses animais. Com esse propósito, entre 2023 e 2025 foram avaliadas 13 fêmeas de tamanduá-bandeira e seis de tatu-canastra de vida livre nos biomas Cerrado e Pantanal, utilizando metodologias consolidadas em espécies domésticas, como avaliação da genitália externa, citologia vaginal, dosagens séricas de estradiol e progesterona e caracterização da microbiota vaginal. Em *M. tridactyla*, a citologia revelou predomínio de células parabasais e intermediárias, com concentrações médias de estradiol de 21,38 ± 8,75 pg/mL nas adultas e 27,38 ± 17,30 pg/mL nas jovens, e de progesterona de 1,97 ± 0,76 ng/mL e 2,42 ± 0,75 ng/mL, respectivamente, sem diferenças significativas; a microbiota vaginal mostrou composição homogênea, dominada por bacilos da família Enterobacteriaceae. Já em *P. maximus*, observou-se ampla variação morfológica da genitália externa, citologia vaginal com predomínio de células parabasais na jovem e maior heterogeneidade nas adultas, além de concentrações médias de estradiol de 422,5 ± 620,4 pg/mL e progesterona de 5,8 ± 3,3 ng/mL nas adultas, e de 10,2 pg/mL e 1,8 ng/mL na jovem; a microbiota também foi composta majoritariamente por bacilos da família Enterobacteriaceae. Esses resultados revelaram correlações significativas entre parâmetros morfológicos, citológicos e hormonais, fornecendo bases preliminares para o desenvolvimento de protocolos de monitoramento reprodutivo dessas espécies ameaçadas.
Validation of reproductive assessment techniques for free living female giant anteaters (Myrmecophaga tridactyla) and giant armadillos (Priodontes maximus)
Keywords: Citologia; Hormônios; Microbiologia; Reprodução; Xenarthra; Cingulata; Vaginal cytology; Microbiota